Rancangan Pembelajaran Berkarakteristik Pembelajaran Inovatif Abad 21 Pada Materi Estimasi Biaya Konstruksi Dengan Model Pembelajaran Project Based Learning Di Smk Negeri 1 Adiwerna - Muljani, Sutji; Bunawar (Cakrawala: Jurnal Pendidikan, 2022)
21st century learning can be defined as learning that provides 21st century skills to students, namely the 4Cs which include: Communication, Collaboration, Critical Thinking and Problem Solving and Creative and Innovative. 21st century learning is important for education in Indonesia today, because education is held to facilitate students so that they can live better in the future, both in terms of social, cultural, economic, and environmental aspects. Modern learning in the 21st century has seven skills that students must possess, namely: (1) Critical Thinking and Problem Solving (2) Collaboration across Networks and Leading by Influence (3) Agility and Adaptability (4) Initiative and Enteroreneurialism (5) Effective Oral and Written Communication (6) Accessing and Analyzing Information (7) Curiosity and Imagination. To prepare for this, appropriate strategies and learning models are needed to respond to it. Teachers and educators are expected to be able to use the best learning model according to the conditions of the students, the learning environment of the students, and the carrying capacity of the students.